(untitled) (ADVANCES IN MECHANICAL ENGINEERING AND TRANSPORT, 2022)
The article is devoted to the study of the influence of the brake control elements of passenger cars on the stability of their braking properties. An analysis of the influence of the uneven braking forces on the wheels of one vehicle axle on the deviation of the distribution of braking forces between the axles from its calculated value was performed. When assessing the error in regulating the distribution of braking forces between the axles of vehicles, three components were taken into account: the theoretical error due to the imperfection of the chosen method of regulation (the difference between the actual calculated control characteristic and the ideal one), the error created due to the instability of the ratio of braking forces on the front and rear wheels, additional error, due to uneven braking forces on the wheels of individual axles. The instability of the braking torques on the front and rear wheels, due to a change in the coefficients of friction of friction pairs, leads not only to a change in the distribution of braking forces between the axles and individual wheels, but also to a decrease in the braking efficiency of vehicles under operating conditions. The instability of the braking torques on the front and rear wheels, due to a change in the coefficients of friction of friction pairs, leads not only to a change in the distribution of braking forces between the axles and individual wheels, but also to a decrease in the braking efficiency of vehicles under operating conditions. A method is proposed that allows to evaluate the quality of regulation of the distribution of braking forces between the axles of the car, taking into account the instability of the braking forces on the wheels.Keywords: automobile, characteristic, stability, braking control, braking properties, braking mechanism, coefficient of friction, distribution of braking forces.